1988
DOI: 10.1149/1.2096170
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Surface Films Formed on Lithium in Dimethoxyethane and Tetrahydrofuran Solutions

Abstract: Surface films formed on lithium metal in dimethoxyethane (DME) and tetrahydrofuran (THF) solutions of LiClO4 , LiAsF6 , and LiSO3CF3 were analyzed using FTIR, SIMS, and XPS spectroscopies. The films formed in both solvents were found to contain lithium alkoxides. The main reaction products detected with FTIR were LiOCH3 in DME, and normalLiOfalse(CH2)3CH3 in THF. SIMS measurements are consistent with this finding. Reaction mechanisms are discussed. When the water concentration in these systems is 0.01M o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
130
0

Year Published

1998
1998
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 154 publications
(138 citation statements)
references
References 13 publications
7
130
0
Order By: Relevance
“…•− in dimethylformamide ͑DMF͒ containing TBAP from cyclic voltammetry and electron spin resonance data. Similarly, Aurbach and co-workers 26 suggested the formation and oxidation ͑reversibly͒ of superoxide ion in O 2 -saturated DME with TBAP on Au and Ag. More recently, Laoire et al 30 reported high reversibility for the ORR/OER on GC in acetonitrile ͑MeCN͒ with TBAP salt, with a reversible redox potential of ϷϪ0.83 V vs Ag/AgCl ͑Ϸ2.10 V Li ͒ for Reaction 6; the large diffusion-limited currents in their RDE measurements support the facile dissolution of the reduction prod-uct͑s͒ in the electrolyte and also confirm a one-electron reduction of oxygen, perfectly consistent with Reaction 6.…”
Section: Discharge Voltage Comparison Of Li-o 2 Air Electrodes With Vmentioning
confidence: 84%
See 2 more Smart Citations
“…•− in dimethylformamide ͑DMF͒ containing TBAP from cyclic voltammetry and electron spin resonance data. Similarly, Aurbach and co-workers 26 suggested the formation and oxidation ͑reversibly͒ of superoxide ion in O 2 -saturated DME with TBAP on Au and Ag. More recently, Laoire et al 30 reported high reversibility for the ORR/OER on GC in acetonitrile ͑MeCN͒ with TBAP salt, with a reversible redox potential of ϷϪ0.83 V vs Ag/AgCl ͑Ϸ2.10 V Li ͒ for Reaction 6; the large diffusion-limited currents in their RDE measurements support the facile dissolution of the reduction prod-uct͑s͒ in the electrolyte and also confirm a one-electron reduction of oxygen, perfectly consistent with Reaction 6.…”
Section: Discharge Voltage Comparison Of Li-o 2 Air Electrodes With Vmentioning
confidence: 84%
“…In addition, the extremely low solubility of lithium ͑per͒oxides and other metal ͑per͒oxides in aprotic solvents leads to the formation of surface films that can poison the electrode in subsequent cycles ͑ORR currents can only be observed in the first voltammetric scan if these surface films are not removed on the oxidation sweep at voltages no greater than 3 V Li ͒. 26,27 Proposed ORR mechanisms in Li ϩ -containing aprotic solvents.-We propose here the ORR mechanism in Li + -containing aprotic solvents. The first step in the ORR in Li + -containing aprotic solvents may proceed according to The sum of Reaction 7a and 7c corresponds to the first reduction step proposed in a recent DFT study on the ORR in Li-air batteries.…”
Section: Discharge Voltage Comparison Of Li-o 2 Air Electrodes With Vmentioning
confidence: 99%
See 1 more Smart Citation
“…The second potential range, between 0.9 and 0.005 V, presents us with a two‐step silicon lithiation (alloying with Li) process that has two peaks at 0.3 V (≈28 µA) and 0.1 V (≈80 µA). Below applied potentials of 0.5 V reduction pathways of linear ethers (e.g., dimethoxyethane) are possible and lithium alkoxides (e.g., LiOCH 2 CH 3 ) are the dominant SEI product …”
Section: Resultsmentioning
confidence: 99%
“…[ 11–19 ] Aurbach was the first to investigate the composition and morphology of various SEIs formed on lithium metal in contact with various liquid electrolytes. [ 20–23 ] Recently, significant efforts have been made in the direction of in situ observation of the initial SEI formation on metallic lithium by electron microscopy, [ 24–27 ] as well as of the SEI growth in contact with solid lithium electrolyte. [ 28 ] However, the evolution of composition, morphology, and thus evolution of ionic and electronic conductivity of the SEI phases under current or voltage (conditions similar to the battery operation) remains to be better understood.…”
Section: Figurementioning
confidence: 99%